Diverse Cell Death Mechanisms Are Simultaneously Activated in Macrophages Infected by Virulent Mycobacterium tuberculosis - Lucero A. Ramon-Luing; Yessica Olvera; Julio Flores-Gonzalez; Yadira Palacios; Claudia Carranza; Yerany Aguilar-Duran; Marco Antonio Vargas; Neptali Gutierrez; Karen Medina-Quero; Leslie Chavez-Galan (Pathogens, 2022)
Macrophages are necessary to eliminate pathogens. However, some pathogens have developed mechanisms to avoid the immune response. One of them is modulating the cell death mechanism to favor pathogen survival. In this study, we evaluated if virulent Mycobacterium tuberculosis (M. tb) can simultaneously activate more than one cell death mechanism. We infected human monocyte-derived macrophages (MDM) in vitro with avirulent (H37Ra) and virulent (H37Rv) strains, and then we measured molecules involved in apoptosis, necroptosis, and pyroptosis. Our data showed that H37Rv infection increased the BCL-2 transcript and protein, decreased the BAX transcript, and increased phosphorylated BCL-2 at the protein level. Moreover, H37Rv infection increased the expression of the molecules involved in the necroptotic pathway, such as ASK1, p-38, RIPK1, RIPK3, and caspase-8, while H37Ra increased caspase-8 and decreased RIPK3 at the transcriptional level. In addition, NLRP3 and CASP1 expression was increased at low MOI in both strains, while IL-1β was independent of virulence but dependent on infection MOI, suggesting the activation of pyroptosis. These findings suggest that virulent M. tb inhibits the apoptosis mediated by BCL-2 family molecules but, at the same time, increases the expression of molecules involved in apoptosis, necroptosis, and pyroptosis at the transcriptional and protein levels, probably as a mechanism to avoid the immune response and guarantee its survival.